Ideenwettbewerb Stadtzentrum Wetter/Ruhr. - (:unkn) unknown (My University, 1977)
1. Preis Jochen Scharf(Köln), 2. Preis Paul Doetsch, Gustav Olbrechts (Köln), 3. Preis Gruppe Hardtber (Bonn), 4. Preis Jochen Boskamp, Borghild Fenina, Jochen Kuhn, Beatrice Stantschev, Michael Wegmann (Düsseldorf), 5. Preis Wilhelm Harde, Peter Scheele (Dortmund), 4 Ankäufe.
Keywords: Städtebaulicher Wettbewerb; Stadtzentrum; Stadtgestaltung; Stadtplanung; Planung